FRIENDLY FEELING SEBAGAI MODAL SOSIAL SISWA DALAM WARGA SEKOLAH MULTIKULTURAL PADA MATA PELAJARAN SOSIOLOGI - Noviana, Mila; Maftuh, Bunyamin; Wilodati, Wilodati (Universitas Tanjungpura, 2022)
Friendly feelings should be applied to students, especially to school members who are very heterogeneous or diverse in terms of ethnicity, religion, skin color, customs, and race. This study aims to describe the sense of friendship or the character of this friendly feeling as students' social capital in school diversity. This research uses a quantitative approach to the type of survey at SMAN 10 Mataram in the Social Sciences department. The results showed that the social studies students, both male, and female, had high friendly feelings. The character of friendly feelings is supported by the application carried out by Sociology teachers through multicultural education with the design of learning models based on local wisdom. The local wisdom that is applied is the local wisdom of the local tribes, such as the traditional song of the nongak lizard, betemue culture, and weaving which can foster a sense of friendliness between students so that it becomes a habit to be able to appreciate a difference. Differences in things that must be disputed will make students collaborate and work well. Local wisdom can be the basis of educational practice.